THE EFFECTS OF DIETARY PROTEIN RESTRICTION ON CHORDA TYMPANI NERVE TASTE RESPONSES AND TERMINAL FIELD ORGANIZATION - THOMAS, J. E. (2008)
Prenatal dietary sodium restriction produces profound developmental effects on rat functional taste responses and formation of neural circuits in the brainstem. Converging evidence indicates that the underlying mechanisms for these effects are related to a compromised nutritional state and not to direct stimulus-receptor interactions. We explored whether early malnourishment produces similar functional and structural effects to those seen following dietary sodium restriction by using a protein deficient, sodium replete diet. To determine if early dietary protein-restriction affects the development of the peripheral gustatory system, multi-fiber neurophysiological recordings were made from the chorda tympani nerve and anterograde track tracing of the chorda tympani nerve into the nucleus of the solitary tract (NTS) was accomplished in rats fed a protein-restricted or a control diet (6% and 20%, respectively). The dietary regimens began on embryonic day 7 and continued until rats were used for neurophysiological recordings (postnatal days (P) 35–50) or for chorda tympani terminal field labeling (P40–50). Responses to a concentration series of NaCl, sodium acetate, KCl, and to 0.50 M sucrose, 0.03 M quinine-HCl, and 0.01 N HCl revealed attenuated responses (30–60%) to sodium-specific stimuli in rats fed the 6% protein diet compared with those fed the 20% protein diet. Responses to all other stimuli were similar between groups. Terminal field volumes were nearly twofold larger in protein-restricted rats compared with controls, with the differences located primarily in the dorsal-caudal zone of the terminal field. These results are similar to the results seen previously in rats fed a sodium-restricted diet throughout pre- and postnatal development, suggesting that dietary sodium- and protein-restriction share similar mechanisms in altering gustatory development.